Targeted delivery of vitamin E TPGS based nanomedicine for treatment of triple negative breast cancer - Rajaletchumy, Veloo Kutty (2015)
Triple negative breast cancers (TNBC) can be classified as one of the most aggressive with a high rate of local recurrences and systematic metastases. TNBCs are insensitive to existing hormonal therapy or targeted therapies such as the use of monoclonal antibodies, due to the lack of estrogen receptor (ER) and progesterone receptor (PR) and the absence of overexpression of human epidermal growth factor receptor 2 (HER2) compared with other types of breast cancers. The absence, of targeted therapies for selective delivery of therapeutic agents (TAs) into tumours, coupled with the multidrug resistance (MDR) which prevents their delivery, leads to the two consequences: the ineffectiveness of conventional chemotherapy on TNBC cells and considerable side effects to healthy cells due to non-specificity of the chemotherapeutic agents. Although nanomedicine has shown superior killing effects on TNBC cells compared with free drugs, there is need to identify the possible targeting agents in order to effectively deliver the nanomedicine into metastatic TNBC cells. At the outset of this study, only a handful of publications have reported the possible targeting agents used in clinical studies for the treatment of TNBCs. From clinical studies, TNBC patients have been found to show superior response rates with the combination therapy of chemotherapy and the anti-EGFR monoclonal antibody, cetuximab, compared with chemotherapy alone. However, the conventional method of delivering both cetuximab and the chemotherapeutic agents as free drugs does not show long term efficacy and therefore leads to a high rate of recurrences. We postulated that novel targeted nanomedicines - by virtue of the ability of nanocarriers to transport drugs specifically into the TNBC cells, comparedwith free drug molecules - could enhance the delivery of chemotherapeutic agents into cells, thereby improving the killing effects and reducing the rate of recurrence. In this study, we developed a targeted micellar system of cetuximabconjugated micelles of D-a-tocopheryl polyethylene glycol succinate (vitamin E TPGS) for targeted delivery of docetaxel as a model anticancer drug for the treatment of TNBCs. The in vitro cytotoxicity studies has shown that TNBC cells exhibited a greater degree of drug resistance than the ER/PR or HER2 positive breast cancer cells after treatment with the free docetaxel drug, Taxotere® (Dox) which is used commercially in clinical studies. Interestingly,the drug resistance can be greatly attenuated by the docetaxel-loaded vitamin E TPGS (TPD) micellar formulation and further still by the cetuximabconjugated, docetaxel-loaded vitamin E TPGS micelles (TPDC) to target the EGFR-overexpressing TNBC cells. Then, we used the EGFR-overexpressing cell line, MDA-MB-231/Luc, to develop the TNBC xenografi model in female CB-17 Severe Combined Immunodeficiency (SCID) mice. The real time in vivo biodistribution and tumour targeting ability of the micelles after intravenous injection (i.v.) were studied by the noninvasive IVIS® imaging system. The anti-tumour effects of the TPGS, docetaxel loaded targeting and non-targeting TPGS micelles were evaluated using the TNBC xenograft model, and compared with Taxotere®. In order to elucidate the behaviours of the cancerous cells after the nanomedicine treatment, we performed explant cultures of the tumours pretreated with one of our micelle formulations, and attempted to re-examine in greater detail whether our drug-micelle system was indeed efficacious through ex vivo investigation. The ex vivo study has demonstrated that tumours treated with targeting micelles exhibited enhanced cell cycle arrest and attenuated proliferation compared with the control and with those treated non-targeting micelles. Furthermore, the ex vivo investigation revealed that both the targeting and non-targeting micellar formulations culminated in antiangio genesis effects and inhibition of metastases. Overall, both the in vivo and ex vivo data increased the confidence that our micellar formulations, TPDC, effectively targeted and inhibited EGFR-overexpreSSing MDA-MB-23 I tumours.